Good night, good night : based on The going to bed book - Boynton, Sandra (Little Simon, an imprint of Simon & Schuster Children's Publishing Division, 2021)
A group of animals, afloat on an ark, go through their nightly bedtime rituals of exercising, toothbrushing, and so on, until two rabbits sing them a lullaby and the sea rocks them to sleep.